A Development HUMAN RESOURCE DEVELOPMENT IN HALAL TOURISM: A CASE STUDY OF THE ISLAMIC TOURIST DESTINATION OF SAPURO TOMB IN PEKALONGAN - Naila Abidah; Gunawan Aji; Hariana Reksa Zakiyya (Ikatan Dosen Menulis, 2023)
This research intends to analyze Human Resource Developmentin Halal Tourism: Case Study of Islamic Tourism Destinations inIndonesia. This research is library research with a qualitativeapproach. The data sources used in this research come fromvarious literature journal articles that are relevant to the researchtopic. The data analysis method used is content analysis of theliterature sources used in the research. From this research it isconcluded that human resources have the potential containedwithin humans to realize their role as adaptive and transformativesocial beings who are able to manage themselves and all thepotential contained in nature towards achieving a prosperous lifein a balanced and sustainable order. Human resources are aprocess of utilizing humans as workers in a humane manner, sothat their physical and psychological potential functions optimallyto achieve organizational goals. Tourism in Indonesia is a placethat has good prospects. With this, Indonesia needs to increase itscapacity to develop management to attract more domestic andforeign tourists. The management itself also requires good humanresources so that it takes from the existing workforce to increasehalal tourism business actors in various regions of Indonesia. Ingeneral, halal tourism is a tourist attraction that has special rulesthat meet the provisions of Islamic law, such as facilities andservices. This halal tourism aims to make a tourist destinationfriendly for Muslim tourists but can still be enjoyed by nonMuslim tourists.